When Novice Therapists Meet Their First Patients: Reflections and Questions on Training in CBT - Huppert, Jonathan D.; Carmeli, Gil; Gilon, Daniel (Pragmatic Case Studies in Psychotherapy, 2008)
Hougaard et al.(2008) report a case series on a mixed individual and group treatment for social phobia, suggesting that the treatment is efficacious. As a group who has just embarked on a similar training program, we comment on their endeavor from the teacher/student perspective with an eye towards pedagogy in training students to conduct CBT. Thoughts and questions regarding the treatment, the patients, the therapists, and the outcomes are raised in order to highlight the potential that exists in such training models.